Feasibility Study Combining Art Therapy or Cognitive Remediation Therapy with Family Based Treatment for Adolescent Anorexia Nervosa - Lock, James (Eur Eat Disord Rev, 2017)
Adolescents with AN who have obsessive-compulsive (OC) features respond poorly to family-based treatment (FBT). This study evaluated the feasibility of combining FBT with either cognitive remediation therapy (CRT) or art therapy (AT) to improve treatment response in this at-risk group. Thirty adolescents with AN and OC features were randomized to 15 sessions of FBT plus CRT or AT. Recruitment rate was 1 per month, treatment attrition was 16.6% with no differences between groups. Suitability, expectancy and therapeutic relationships were acceptable for both combinations. Correlations between changes in OC traits and changes in cognitive inefficiencies were found for both combinations. Moderate changes in cognitive inefficiencies were found in both groups but were larger in the FBT plus AT combination. This study suggests that an RCT for poor responders to FBT because of OC traits combining FBT with either CRT or AT is feasible to conduct.